The Influence of Service Quality and Company image on customer Trust at PT PLN (Persero ) UID SULUTTENGGO - Nafai, Rakhel Gloria Benedikta; Pio, Riane Johnly; Walangitan, Olivia F.C (Productivity, 2025)
This study was motivated by various service-related issues faced by PT PLN (Persero) UID SULUTTENGGO, such as unscheduled power outages, slow handling of disturbances, and unstable voltage supply. These problems have the potential to reduce customer trust in the company. The purpose of this research is to analyze the influence of service quality and corporate image on customer trust. The main theoretical framework used is the SERVQUAL model by Parasuraman, Zeithaml, and Berry (1988), which includes the dimensions of reliability, responsiveness, and empathy. For corporate image, the theory from Rajagukguk (2015) was used, covering aspects such as reputation, personality, values, and company identity. His study applies a quantitative approach using a survey method and multiple linear regression analysis. Data were collected from 124 respondents using a Likert-scale questionnaire. The results show that both service quality and corporate image have a positive and significant influence on customer trust, with regression coefficients of 0.346 for service quality and 0.364 for corporate image. The Adjusted R Square value of 0.677 indicates that 67.7% of the variation in customer trust can be explained by the two independent variables. Theoretically, this research contributes to the literature on customer trust in the context of public service monopolies. Practically, the findings provide valuable insights for PT PLN to improve service reliability, enhance responsiveness to customer complaints, and strengthen the company’s image through innovation and corporate social responsibility. By focusing on these areas, the company can build stronger and more sustainable customer trust.